On the Relevance of Jesus Christ for Christian Judgements About the Legitimacy of Violence: A Modest Proposal - Clough, David (Studies in Christian ethics, 2009)
This article surveys traditional and modern interpretations of Jesus' teaching on violence in the Sermon on the Mount, showing that from Augustine onwards and for a wide variety of reasons Christians have taken the view that the teaching and example of Christ about violence cannot be squared with the necessity of being violent in the context in which they find themselves. Against this position, the article makes the modest proposal that the Church will decide best about the ethics of violence when it recognizes that the teaching and example of Jesus Christ are relevant to the question.